A randomized controlled trial comparing oxytocin administration before and after placental delivery in the prevention of postpartum haemorrhage in a tertiary care hospital in Bankura district of West Bengal, India - Kirtania, Rahul; Pal, Jayita; Biswas, Sisir; Aich, Aditi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: PPH is the prime cause of maternal mortality worldwide. The incidence of PPH can be drastically combatted by application of uterotonic in active management of third stage labour. Timing of its administration is a matter of concern. This study aimed to assess whether timing of administration of oxytocin would have any impact on incidence or mean blood loss of PPH. Methods: It was a single blinded randomized controlled trial conducted in the department of Obstetrics and Gynecology, Bankura Sammilani Medical College for 6 months where 100 antenatal mothers admitted for normal delivery in labour room were allocated randomly in study and control group considering inclusion and exclusion criteria. Incidence of PPH and mean blood loss had been identified clinically by following them for 24 hours. Results: Only 9% of study population had experienced PPH. There was no statistically significant difference in incidence of PPH with difference in timing of administration of oxytocin (p >0.05). But there was statistically significant decrease in mean blood loss if oxytocin was administered before the placental delivery. The mean blood loss with oxytocin administered before placental delivery was 296.8 ml (102.45) and after placental delivery was 452.0 (128.87) ml respectively. Conclusions: Policy makers should keep in mind not only the incidence of PPH, but the mean blood loss amount too in a setting where anaemia in pregnancy is quite prevalent.